Report of the administration of the British-United States : Zone of the free territory of Trieste : 1 october to 31 december 1948: Report number 5 - Airey, T.S. (Trieste : Arti grafiche "Smolars", 1949)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: territoriale kwesties; Trieste